Maintaining Mandar Silk Fabric Through Addressing and Marketing as a Supporter of Marital Tourism at Polewali Mandar - Muhammad Yusuf (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This research aims to find out: 1) how the Mandar community cadre system improves Mandar women's skills in weaving; 2) what is the marketing system used in marketing Mandar silk products. This research is applied research with a qualitative approach. Data were analyzed descriptively. Research data was obtained from interviews, observation and documentation. The data analysis technique used in this research is descriptive data analysis technique. Observations were made in one of the sub-districts which has many weavers, especially in Karama village and Napo village as villages that produce a lot of Mandar silk weaving works. The results of the research show that: 1) The formation of young women is still carried out conventionally, not formally, such as through formal education in public schools. 2) The marketing system they use still uses conventional methods.